Peningkatan Mutu Perguruan Tinggi Kegamaan Islam Melalui Penyusunan Manajemen Strategis Dengan Pendekatan Balanced Scorecard: Studi Kasus di STAI Sangatta Kutai Timur - Zamroni Zamroni; Siti Nasiah (FENOMENA, 2018)
College has an important role in nation building. Therefore, university governance systems need to get serious attention and appropriate management touches. One of the modern management concepts that can be used is balanced scorecard, which is expected to improve the quality of the institution. This research uses qualitative approach of case study type with research setting at STAIS Sangatta Kutai Timur. The results showed that; improvement of education quality in STAIS Sangatta Kutai Timur is done through; 1) visionary leadership, 2) internal and external environmental analysis done with SWOT analysis, 3) to make quality as "Spirit" in every organizational activity by implementing quality-based, oriented management; a) Costumer Satisfaction, b) continous improvement, c) full involvement of the academic community, d) continous improvement. In order to improve the quality of education with Balanced Scorecard approach, STAIS Sangatta Kutai Timur focuses on four perspectives, namely; financial perspective, costumer perspectives, internal perspectives and development perspectives of development and growth are very effective in improving the quality of education. From several Balanced Scorecard perspectives applied in STAIS Sangatta Kutai Timur, the most dominant internal perspective on the effectiveness of quality improvement of education, followed by learning and growth perspective, costumer and finansial.